Производительность процесса шлифования стальных деталей - Корчак Станислав Николаевич (Машиностроение, 1974)
Экземпляры: КХ (20200427) / Инвентарный номер: 592198 / Сис.шифр: 621.92 / Авт.знак: К 70 / ГРНТИ: 81 / ББК: 34